AZAS CONTRADICTOIRE DELIMITATIE DALAM PENDAFTARAN TANAH - Ferdy Nugraha (UNES Law Review, 2022)
The principle of contradictoire delimitatie is a rule in the land registration process where there is an agreement between the land owner and the owner of the adjacent land parcels. The Land Office of the Mentawai Islands Regency received Land Registration activities and experienced an increase in volume from 2017 to 2021. In its implementation, does it meet the principles of the contradictoire delimitatie principle as a whole. The research method used is an empirical juridical legal research method using several legal theories as an analytical knife. The results showed that the application of the contradictoire delimitatie principle in land registration experienced two conditions, namely implemented and not implemented. The contradictoire delimitatie principle which is not implemented has several impacts, namely the absence of legal certainty and legal protection for the subject and object of the land parcel. As for the creation of the principle of contradictoire delimitatie as a whole, it is necessary to carry out a movement to install joint boundary markings as a form of orderly land administration.